State Visit of the Prime Minister of Nepal to India: Media and Public Perception (Sudurpaschim Spectrum, 2024)
This study delves into the media representation and public perception towardsofficial visits by Nepali Prime Minister to India, analyzing Indian media outlets' framing of power dynamics, strategic messaging, perception management, economic interests, and regional dynamics in Nepal-India relations. As part of the study methodology, the researcher deliberately chose seven prominent Indian online media sites and examined the contentsthese platforms produced about the state visit of the prime minister of Nepal to India on multiple occasions.The study also analyzes the language, rhetoric, and framing used by media outlets while reporting on the state visit. It employs critical and agenda setting theory in international relations to uncover underlying power structures and ideologies in media coverage and agenda-setting theory to examine how media narratives influence public opinion and policy priorities. The analysis reveals a complex interplay of interests, strategies, and perceptions shaping the evolving Nepal-India relationship, highlighting the multifaceted nature of international relations. The study finds that the media coverage reflects a nuanced understanding of power dynamics between Nepal and India, highlighting the strategic maneuvers of Nepali leaders to convey messages of cooperation, reorientation of foreign policy, and correction of perceived images, especially concerning China. This demonstrates how leaders strategically navigate international relations to shape perceptions and relationships.